Biodistribution and elimination characteristics of two 111In-labeled CCK-2/gastrin receptor-specific peptides in rats - Trejtnar, Frantisek; Laznicek, Milan; Laznickova, Alice; Kopecky, Martin; Petrik, Milos; Béhé, Martin; Schmidt, Jörg; Maecke, Helmut; Maina, Theodosia; Nock, Berthold (Anticancer research, 2007)
BACKGROUND: Due to their high CCK-2/gastrin receptor selectivity, high affinity, and rapid background clearance, radiolabeled minigastrins (MG) are emerging as promising new tools in the diagnosis and therapy of CCK-2/gastrin receptor-positive tumors. In this study, the pharmacokinetic profile, particularly the excretion mode, of two 111In-labeled minigastrins was compared in rats. The first tracer, 111In-MG-0 is based on (D)Glu1-MG, while the second, 111In-MG-11, is its des-(Glu)5-derivative, expected to be less retained in renal tissue. MATERIALS AND METHODS: The fate of 111In-MG-0 and 111In-MG-11 in the body of rats was investigated during biodistribution and bioelimination experiments, while the respective elimination parameters were determined in perfused rat liver and kidney models. RESULTS: During biodistribution both compounds were rapidly cleared from the blood and most non-target organs whereas activity levels in the bowel and stomach declined slowly. The overall contribution of hepatobiliary excretion of 111In-MG-0 and 111In-MG-11 was relatively small. In the perfused rat liver their elimination into the bile was negligible. In contrast, renal excretion was the major excretion pathway for both analogs, mainly via glomerular filtration. However, kidney levels were substantially higher and retention was more prolonged in the case of 111In-MG-0 as compared to 111In-MG-11. CONCLUSION: The presence of the (Glu)5-chain in 111Ln-MG-0 appears to be implicated in the prolonged radioactivity retention in the kidney of rats.
Keywords: játra; Substrate Specificity; cholecystokinin; receptor cholecystokininu B; Oligopeptides; ledviny; tkáňová distribuce; Kidney; krysa rodu Rattus; Indium Radioisotopes; zvířata; oligopeptidy; Cholecystokinin; potkani Wistar; Perfusion; Receptor, Cholecystokinin B; Isotope Labeling; Peptide Fragments; izotopové značení; Liver; Rats, Wistar; Male; substrátová specifita; radioizotopy india; perfuze; peptidové fragmenty; Rats; Gastrins; Animals; mužské pohlaví; radiofarmaka; Tissue Distribution; gastriny; Radiopharmaceuticals